Ministry of Tourism and Culture (MOTAC) / Muhamad Asyraf Asbar ... [et al.] - Asbar, Muhamad Asyraf; Mohd Zahir, Muhammad Afiq; Mohd Jamiran, Nur Shamirah; Afandi, Nur Fatin Syamimi (2018)
Ministry of Tourism and Culture (MOTAC) is to serve the close connection between tourism and culture in efforts to promote Malaysia as a top-of-the-mind destination, in line with its ever popular tagline “Malaysia, Truly Asia”. MOTAC provide many facilities and services that ease the occupant in the building. Furthermore, MOTAC’s building have different tenants and gross floor area by each level. Building maintenance is important in building to preserve the physical characteristics of a building and its services. Such as fewer breakdowns and lower future maintenance costs, higher productivity, and less wastage of materials and improve organization sales re venue. In MOTAC most of the maintenance work are be done by the Peransang Jati Sdn. Bhd. So the JKR hired an out source contractor for the maintenance work to improve condition of the building gives positive effect to the users resulting in lower staff turnover, better customer relation and public image. With the standards that be follow, the policy that be stated also can be perpendicular with rules and regulations. The maintenance programme are the biggest impact that helps to maintain the building so it can be used within certain period of time and in MOTAC the Planned Preventive Maintenance are being used as guidelines to the maintenance programme. Next, we also learnt about the building elements and specification for the MOTAC building which is consist of super structure, internal finishes and joinery fittings, special technologies and features that have been installed and being used in MOTAC building. We learnt to apply all CPBS101 book in our task assignment. We also required to inspect the entire building which is internal and external area. This requirement is including internal and external façade, fabric and component and also services. Maintenance Strategy is defined as a long-term plan, covering all aspects of maintenance management for achieving a desired future state for the maintenance function. Then, we discovered that MOTAC had comply all of the laws and regulations related to the building based on Uniform Building By Law 1984 (UBBL 1984), Act 133, Street, Drainage & Building 1974, Occupational Safety and Health 1984 (OSHA) and Electricity Supply Act 1990 (ACT 447). The purpose of these acts is so that the building meets its requirements and specifications. Ministry of Tourism and Culture (MOTAC) has their maintenance budget or its final statemen